Eliciting the contribution of TiN to photoelectrochemical performance enhancement of Imma-LaTiO2N at neutral pH. (July 2022) - Hojamberdiev, Mirabbos; Mora-Hernandez, Juan Manuel; Vargas, Ronald; Heppke, Eva Maria; Yubuta, Kunio; Yamakata, Akira; Kadirova, Zukhra; Torres-Martínez, Leticia; Teshima, Katsuya; Lerch, Martin
Abstract: The presence of defects, which act as the recombination hubs for photogenerated charge carriers, hinders the improvement of photocatalytic activity for oxygen evolution reaction of LaTiO2 N under visible light irradiation via a four-electron-transfer reaction pathway. Here, we involve titanium nitride (TiN) in a varying content (0–17.8%) to improve the efficiency of charge separation and transport, influencing the photoelectrochemical performance of LaTiO2 N. The characterization results confirm the formation of a strong contact between orthorhombic-LaTiO2 N and cubic-TiN particles. The photoelectrochemical (PEC) measurements reveal the inverse dependence between electron transfer phenomena and charge carrier recombination, which allows to understand the trend when modifying LaTiO2 N with TiN. In fact, the incorporation of 17.8% TiN in the LaTiO2 N:TiN material results in a higher photocurrent. Open-circuit potential (OCP) decay and transient absorption spectroscopy (TAS) studies confirm longer lifetimes of charge carriers for increasing amounts of TiN in the synthesized materials. Thus, the main role of TiN is to improve the properties of the semiconductor-electrolyte interface, having verified its impact on the separation and transport of photogenerated charge carriers. Furthermore, computational studies predict that the adsorption of water molecules is favored at the LaTiO2 N:TiN surface compared to the individual TiN and LaTiO2 N surfaces. Graphical abstract: Image 1 Highlights: Titanium nitride is involved to improve the efficiency of LaTiO2 N. TiN content influences charge separation and transport. 17.8% TiN in LaTiO2 N:TiN generates a higher photocurrent. Longer lifetimes of charge carriers are achieved by adding TiN. Water adsorption on the LaTiO2 N:TiN surface is also favored.